Господарсько-біологічні особливості, адаптаційні властивості свиней ірландського походження та їх використання за різних методів розведення - Храмкова, Ольга Миколаївна; Khramkova, O.; Khramkova, O. M.; Khramkova, O. N.; Hramkova, O. N.; Khramkova, Olga (Миколаївський нац. аграрн. ун-т, 2021)
Дисертація на здобуття наукового ступеня кандидата сільськогосподарських наук за спеціальністю 06.02.01 – розведення та селекція тварин – Миколаївський національний аграрний університет Міністерства освіти і науки України. – Миколаїв, 2021. Дисертаційна робота присвячена оцінці господарсько-біологічних особливостей, адаптаційних властивостей свиней ірландського походження та їх використання за різних методів розведення для одержання комерційних гібридів в умовах України. В умовах промислового господарства Степу України встановлено що найкращою материнською формою для гібридизації є поєднання (♀Й×♂Л) ірландської селекції при їх схрещуванні з кнурами лінії «MaxGrow» ірландської селекції. Доведено, що відгодівельні показники фінальних гібридів є кращими за використання в якості материнської форми свиноматок F1 (♀Лі×♂Йі) у поєднані з кнурами синтетичних ліній зарубіжного походження, порівняно із поєднаннями тих же кнурів зі свиноматками F1 (♀Йі×♂Лі). Визначено, що свиноматки вітчизняної селекції, порівняно з аналогами зарубіжної як при чистопородному розведенні, так і при схрещуванні відрізняються кращим на 0,12-0,24 бали коефіцієнтом адаптації та на 0,4-5,4 бали індексом теплостійкості. Встановлено, що тварини зарубіжних генотипів перевершували своїх ровесників вітчизняної селекції за виходом м’яса на 2,7-4,2%, водночас, якісні показники м’яса були кращими у тварин вітчизняної селекції. Доведено, що сила впливу породних поєднань на вміст м’яса в туші вірогідно склала 27,3%, а передзабійна жива маса мала силу впливу на цей показник 6,0%. Thesis for obtaining the scientific degree of the Candidate of Agricultural Sciences in the specialty 06.02.01 – Animal Breeding and Selection. – Mykolayiv National Agrarian University of the Ministry of Education and Science of Ukraine. – Mykolayiv, 2021. The dissertation is devoted to the assessment of economic and biological features, adaptive properties of Irish origin pigs and their use with different breeding methods to obtain commercial hybrids in Ukraine. In the conditions of industrial farming of Ukrainian steppe, it is established that the combination (♀Y×♂L) of Irish origin is the best maternal form for hybridization when sows are crossed with boars of the "MaxGrow" line of Irish selection. It is proved that the fattening indicators of the final hybrids are better with the use of F1 (♀Lі×♂Yі) sows as the maternal form in crossing with boars of synthetic lines of foreign origin compared to crossing the same boars with F1 (♀Yі×♂Lі) sows. It is determined that sows of native selection in comparison with foreign ones, both during pure-breeding and crossing, differ in the coefficient of adaptation better by 0.12-0.24 points and the heat resistance index better by 0.4-5.4 points. It is found that stress-sensitive piglets were absent among the offspring of native animals, while they were found in the amount of 6% among purebred piglets of Irish origin. All local piglets of different genetic combinations had more stress-sensitive individuals than purebred ones. The most sensitive to stress were animals with high nominal blood relationship of Danish Landrace breed (18- 33%). It is found that pigs of foreign origin had greater weight loss during transportation compared to native animals. The increase of pre-slaughter weight of pigs to 120 kg led to a decrease of weight loss during transportation by 0.2-0.3%. The impact of the breed crossing on weight loss during transportation was 33.1%, while the weight loss was 7.36%. It is found that animals of foreign genotypes exceeded their domestic peers in meat yield by 2.7-4.2%, while the quality of meat was better in native animals. In animals of all experimental genotypes, with an increase of pre-slaughter weight from 100 to 120 kg, the thickness of the back fat, the mass of the ham, and the area of the "ribeye muscle" increased significantly. The meat yield, with an increase of preslaughter weight by 20 kg, decreased less in the carcasses of animals of foreign selection compared to the carcasses of animals of native selection. It is shown that the impact of breed crossing on the meat content in the carcass was about 27.3%, while the pre-slaughter live weight had an impact on this figure about 6.0%. It is proved that the meat of animals of all experimental groups had a level of acidity and moisture retention within the norm, according to the European category NOR (normal). Meat of animals of native selection, with both slaughter weight of 100 and 120 kg, has the best quality indicators. It is found that the meat of animals obtained from intensive commercial genotypes of foreign selection has a higher protein content and lower fat and ash content compared to the meat of native pigs. It is proved that the most economically advantageous is the fattening of pigs obtained from a combination of "MaxGrow" boars with Li × Yi and Yi × Li sows up to a live weight of 120 kg, where the level of profitability is 63%.
Economic and biological features, adaptive properties of Irish origin pigs and their use with different breeding methods
Храмкова Ольга Миколаївна http://orcid.org/0000-0002-0697-7715
Keywords: фізико-хімічні властивості; physicochemical properties; свині; pigs; методи розведення; breeding methods; зарубіжні генотипи; foreign genotypes; комерційні гібриди; commercial hybrids; термінальна лінія; terminal line; відтворні якості; reproductive qualities; відгодівельні якості; fattening qualities